Coordinated Meaning Management In The Successful Reconstruction of The New Identity Negotiations of The Anies-Muhaimin Pair In The 2024 General Election In Sidoarjo District - Tri Widyana Putri, Erisanti; Dwi Prasetyo, Bambang (Dinasti Research, 2024)
This research focuses on Coordinated Meaning Management (CMM) in successfully reconstructing the Anies-Muhaimin pair's identity negotiations in the 2024 elections in Sidoarjo Regency. The main objective of this research is to explore how the pair's political communication and branding strategies were able to influence and convince voters in Sidoarjo Regency who have a strong culture with NU (Nahdlatul Ulama). The research methodology used primary and secondary data collected through observation, interviews, and documentation based on Creswell's (2007) data collection techniques. Data analysis was conducted using the Miles, Huberman, and Saldana (2014) approach which includes data collection, data condensation, data display, and conclusion drawing/verification. The results showed that the communication strategy built by the Anies-Muhaimin pair through cultural approaches, content, speech acts, and interpersonal relationships was able to change the negative stigma against Anies Baswedan. The hierarchy of meaning of CMM theory proved its relevance in the analysis of field strategies to gain Sidoarjo community sympathizers, although the episode variables in this theory did not have a significant impact.